Smart speakerphone; Queueing simulator for finite queueing system; Infinite queueing simulator by using simscript II.5; Performance analysis of common channel signalling no.7; Traffic routing for common channel signalling no.7; Design of interface unit for rural telecommunication / [mikrofilem] - Ahmad Haizal Hamzah; Chang, Ming Soon; Koh, Tiong Sern; Razali Awang; Rosman Mohd. Zin; Shamzumi Yusof (Sekudai : UTM, 1995)
Project paper (Bachelor of Electrical Engineering) - Universiti Teknologi Malaysia, 1995